Pharmacognostic Evaluation of Ten Species of Medicinal Importance of Cecropia: Current Knowledge and Therapeutic Perspectives - Rivera-Mondragón, Andrés; Ortíz, Orlando O.; Gupta, Mahabir P.; Caballero-George, Catherina (Planta Medica, 2021)
This work covers a systematic review of literature about the genus Cecropia from 1978 to 2020, emphasizing the analysis of 10 of the most relevant species and their associated biological activities. Cecropia is a neotropical genus, which comprises about 61 native species in the American continent where it is known to be part of the traditional medicine of numerous countries. Secondary metabolites described for this genus showed an elevated structural and functional diversity, where polyphenols have been the most abundant. Based on this diversity, Cecropia phytochemicals represent an important source of potential therapeutic agents yet to be exploited. This review also highlights the effectiveness of combining chemometrics and ultra-performance liquid chromatography-tandem mass spectrometry as a novel approach to successfully single out Cecropia species phytochemicals. While the medicinal use of Cecropia species is officially recognized in National Pharmacopoeias and Formularies of several Latin American countries, it is important to recognize that these phytomedicines are complex mixtures requiring a thorough understanding of their chemical composition and their correlation with biological activities to guarantee their quality, safety, and efficacy.
Keywords: Urticaceae; Cecropia; diabetes; hypertension; flavonoids C-glycosides; ethnobotany